Pengaruh Biaya Promosi dan Biaya Distribusi Terhadap Penjualan Pada PT. Unilever Indonesia Tbk. Tahun 2015-2019 - Ratna Ratna; Nadiatul Khoiroh; Muhammad Ridho (CITRA EKONOMI, 2021)
This study aims to determine the effect of promotion costs and distribution costs on sales at PT. Unilever Indonesia Tbk. 2015-2019.In this research, we will look for how the promotion costs, distribution and sales costs, and the effect of promotion costs and distribution costs on sales. In analyzing the data, testing was carried out using multiple regression analysis. This is done because there are two independent variables, namely promotion costs and distribution costs. Then to find the effect used the t test, f test, and the coefficient of determination. The results showed that the promotion costs at PT. Unilever Indonesia Tbk in 2015-2019 continues to increase each year. The same is the case with the distribution costs from 2015-2019 which tend to continue to increase each year. Likewise, sales from 2015-2019 continue to increase each year. The results of hypothesis testing on the influence of the Promotion Cost variable on Sales show that the t value is 2.433> from t table 1.7396 and the significance value is (sig) 0.026 <from the level of significance (α) 0.05 (5%). This promotion has an influence on sales. The results of testing the distribution cost variable hypothesis on sales that the t value is 13.805> from t table 1.7396 and the significance number is sig) 0.000 <from the level of significance (α) 0.05%, it can be seen that this distribution cost has an effect on sales. The results of the hypothesis testing for the variable promotion costs and distribution costs on sales show that the F value counts 1350,783 with a significance level of (0,000 <0.05), the F table value is 3.59 (1350,783> 3.59), this means that Promotion Costs (X1) and Distribution Costs (X2) have a positive effect simultaneously or together on Sales at PT. Unilever Indonesia Tbk in 2015-2019. The resulting Adjusted R Square is 0.993. So, it can be concluded that the percentage of influence of leadership and job sanctions on employee work discipline is 99.3% and 0.7% is influenced by other variables not examined in this study.